The Use of Learning Media Motion Graphics Towards Students Mathematical Understanding - Ikman Nurhakim Rahadi; Darwan Darwan; Hendri Handoko (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2020)
Learning about the concept and structure of a mathematical material and looking for relationships between them is real math learning. In many math learning materials, students often struggle to understand the concept of the material. The mathematical skills need to be stimulus and encouraged when learning. To practice such skills need innovations such as using motion graphics learning media. The purpose of this research is to know the student's response to the use of motion graphic media, to find out how much the mathematical skills of students after using motion graphic learning media, to know how much influence The media use of motion graphic learning to the students mathematical skills, to determine the effectiveness of the use of motion graphic learning media to the students mathematical skills. This method of research is experimental research with data collection techniques using poll and observation for variable X and test for variable Y. Population for this research is all students of grade IX SMP IT Umar Al Khattab Gunung Jati Kabupaten Cirebon, while the sample Taken by the cluster method of random sampling with the elected class IX B SMP IT Umar Al Khattab Gunung Jati Kabupaten Cirebon. Based on the results of the data processing, the student response questionnaire was obtained against the use of media in motion graphic media learning with an average of 85.23% with very strong criteria. Based on the hypothesis test result obtained tcount > ttable = 9,895 > 2.063, then H0 rejected or Ha is acceptable, the use of Motion graphics Learning Media is effective against the mathematical understanding of grade IX students SMP IT Umar Al Khattab. It is also supported through an N-Gain value of 65.40 as well as an indicator of the learning effectiveness of a KKM pass of 91.66% classifying, student response 85.23%, student activity of 77,,33%, as well as the ability of the teacher to manage the class that got the value 3.34.